Absorptive Capacity and FDI Spillovers: Evidence from Quantile Regressions. Issue 4 (8th August 2017) - Fatima, Syeda Tamkeen
ABSTRACT: Using Turkish firm-level data for the period 2003–2010, we look at the relationship between foreign direct investment, absorptive capacity, and spillovers at a disaggregated level, and analyze whether firms operating in different quantiles of the productivity distribution respond differently to foreign presence and changes in absorptive capacity. The results reveal that, for a given level of foreign presence, it pays to increase the absorptive capacity of firms operating in lower quantiles. When it comes to inter-industry spillovers, it is counterproductive to increase the absorptive capacity of firms already operating in higher quantiles, as this diverts resources from other productive activities.